Reproductive physiology of Ethiopian wolves (Canis simensis) - van Kesteren, F (2011)
Cooperative breeding can be defined as a breeding system in which more than a pair of individuals help rear young from a single litter. Ethiopian wolves, Canis simensis, like many other canids, breed cooperatively. However, unlike most group living canids, they specialize in hunting rodents and forage solitarily. Their unusual social system, which combines cooperative breeding, intense sociality and solitary foraging, makes Ethiopian wolves a suitable species in which to study the physiology of cooperative breeding. There are no Ethiopian wolves in captivity, but advances in reproductive science have enabled researchers to study the reproductive physiology of wild populations non-invasively by extracting and assaying hormones in faecal samples using radio/enzyme immunoassays. Using these methods I studied the reproductive physiology of Ethiopian wolves in Bale Mountains National Park, Ethiopia, the largest population of these rare endemic canids. Faecal samples must be preserved almost immediately after defecation to prevent bacterial degradation of hormones. Freezing is the preferred storage method under controlled conditions, but is often infeasible when studying wild populations. Comparison of three alternative storage methods determined that desiccating samples was a reliable method of preserving Ethiopian wolf samples in field conditions. Analysis of faecal samples collected from 14 dominant and nine subordinate female Ethiopian wolves revealed that dominant females came into oestrus and showed oestradiol peaks during the annual mating season, whereas subordinate females did not, suggesting a hormonal mechanism of reproductive suppression. However, two subordinate females came into oestrus outside the annual mating season. Both dominant and subordinate females had increased levels of progesterone during the duration of the dominant’s pregnancy, and three subordinate females showed signs of pseudopregnancy, including lactation. These results suggest that some subordinate females come into oestrus outside the mating season and become pseudopregnant, as pseudopregnancy in canids follows an infertile ovulation. Dominant females did not prevent subordinate females from mating, and cortisol levels of dominant and subordinate females did not differ significantly during the mating season, suggesting that reproductive suppression in female Ethiopian wolves was unrelated to aggression or stress hormones. No seasonal patterns in testosterone levels in samples collected from male Ethiopian wolves were found. Subordinate males were observed engaged in mating behaviour, including with their pack’s dominant female, but dominant males would prevent subordinate males from mating with the dominant female, suggesting a behavioural method of reproductive suppression. Dominant males had higher cortisol levels than subordinates, which may be related to the stress of maintaining dominant status and/or mate guarding. In summary, seasonal patterns in progesterone and oestradiol levels were found in female Ethiopian wolves, but not in testosterone levels in males. There was evidence for hormonal and behavioural reproductive suppression of subordinate females and males respectively, but in neither sex was reproductive suppression mediated through stress hormones. As well as providing an insight into the reproductive physiology of a rare cooperatively breeding canid, this study provides needed reproductive biology information for a hitherto unstudied species, and sets the basis for making a contribution to future reproductive management initiatives for the conservation of this charismatic canid.